Thirty Years of Herd Behavior in Financial Markets: A Bibliometric Analysis - Espinosa-Mendez, C (Elsevier Ltd, 2022)
Bibliometric studies have proven useful in helping researchers better explore the current research trends within a particular field of study. This study analyzes academic research on herd behavior in financial markets conducted over 30 years. The Web of Science database was selected to collect bibliographic material and provide various bibliometric indicators, including the number of citations, publications, and authors, while bibliometric techniques were also employed for visualizing the similarities. The results show a significant growth in research on herd behavior, especially following the subprime crisis. The concluding results from the literature indicate that there is no consensus regarding the causes of this phenomenon, but new perspective have emerged to expand research on herd behavior. © 2021 Elsevier B.V.